2018
DOI: 10.1093/annonc/mdx684
|View full text |Cite
|
Sign up to set email alerts
|

Sequential chemotherapy/radiotherapy was comparable with concurrent chemoradiotherapy for stage I/II NK/T-cell lymphoma

Abstract: In stage I/II NK/T-cell lymphomas, when effective chemotherapeutic regimens were used, CCRT and sequential CT + RT gave similar outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 16 publications
2
62
1
Order By: Relevance
“…Recently, multicentric studies demonstrated that non-ANT-based CT followed by RT yielded survival comparable to concurrent chemoradiotherapy in early-stage ENKTCL. 27,28 Others have indicated that early or upfront RT results in better survival than late RT for early-stage patients treated with ASP-based or gemcitabine-based CT. 29,30 However, it is difficult to accurately assess the effect of RT timing on outcomes in small cohorts. We hypothesized that the clinical advantage of early RT depends on the initial response to induction CT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multicentric studies demonstrated that non-ANT-based CT followed by RT yielded survival comparable to concurrent chemoradiotherapy in early-stage ENKTCL. 27,28 Others have indicated that early or upfront RT results in better survival than late RT for early-stage patients treated with ASP-based or gemcitabine-based CT. 29,30 However, it is difficult to accurately assess the effect of RT timing on outcomes in small cohorts. We hypothesized that the clinical advantage of early RT depends on the initial response to induction CT.…”
Section: Introductionmentioning
confidence: 99%
“…However, only systematic chemotherapy has the potential to cure patients with advanced or disseminated disease [9,14,35]. Due to the heterogeneity of the disease and variations in the combination and intensity of the first-line treatment for earlystage patients (single modality with radiotherapy or chemotherapy, different sequences of radiotherapy and chemotherapy, various chemotherapy regimens of different intensities) [7,8,12,21], it is important to improve risk stratification models, especially for such a large cohort. In the present study, despite improved survival (5-year OS, 75.5%) with current treatment strategies, the 5-year OS rates for early-stage patients varied substantially from 56.3 to 85.4% when stratified by the NRI into risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our institutional ethics review board approved the study and waived the need for informed consent, as patients had been de-identified in the dataset. Given the wide use of new chemotherapy regimens and modern radiotherapy in the past decade [21,22], the eligibility criteria for this validation study included: (1) patients who had received initial treatment between 2008 and 2016; (2) patients who had received non-anthracycline-based chemotherapy with or without radiotherapy, or radiotherapy alone as the first-line treatment. The exclusion criteria were: (1) patients treated before 2008; (2) anthracycline-based or unknown chemotherapy regimens; (3) dataset from the study of our original nomogram.…”
Section: Eligibility Criteria and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 303 patients, the impact of types of treatment on CR, OS, and PFS rates is evaluated. When effective chemotherapeutic regimens are used, concurrent and sequential chemoradiotherapy give similar outcome . Another multicenter retrospective study of 215 patients compares the efficacy of L‐saparaginase/pegaspargase‐based sequential versus sandwich chemoradiotherapy.…”
Section: Treatmentmentioning
confidence: 99%